2018
DOI: 10.1371/journal.ppat.1007105
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-11-dependent pyroptosis of lung epithelial cells protects from melioidosis while caspase-1 mediates macrophage pyroptosis and production of IL-18

Abstract: Infection with Burkholderia pseudomallei or B. thailandensis triggers activation of the NLRP3 and NLRC4 inflammasomes leading to release of IL-1β and IL-18 and death of infected macrophages by pyroptosis, respectively. The non-canonical inflammasome composed of caspase-11 is also activated by these bacteria and provides protection through induction of pyroptosis. The recent generation of bona fide caspase-1-deficient mice allowed us to reexamine in a mouse model of pneumonic melioidosis the role of caspase-1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 37 publications
2
75
0
Order By: Relevance
“…[80][81][82][83] It has been suggested that as some of these cells do not express the inflammasome component, caspase-11 is responsible for the inflammasome response to infections, probably by direct biding of LPS. 84 These differential results highlight the importance of analysing the expression of inflammasome components in the lung epithelial cell lines before conducting inflammasome experiments and the need to work in mouse and human primary cells.…”
Section: Lung Epitheliummentioning
confidence: 97%
See 1 more Smart Citation
“…[80][81][82][83] It has been suggested that as some of these cells do not express the inflammasome component, caspase-11 is responsible for the inflammasome response to infections, probably by direct biding of LPS. 84 These differential results highlight the importance of analysing the expression of inflammasome components in the lung epithelial cell lines before conducting inflammasome experiments and the need to work in mouse and human primary cells.…”
Section: Lung Epitheliummentioning
confidence: 97%
“…For instance, the involvement of caspase‐1 is not clear because some studies show that epithelial cell lines (Beas2Bs, 16HBE, Calu‐3) and also primary cells (human bronchial epithelial cells) express little to no caspase‐1 in an infection model, whereas others show a role for caspase‐1 in epithelial cells (for instance in Beas2Bs, mouse tracheobronchial epithelial cells and A549) . It has been suggested that as some of these cells do not express the inflammasome component, caspase‐11 is responsible for the inflammasome response to infections, probably by direct biding of LPS . These differential results highlight the importance of analysing the expression of inflammasome components in the lung epithelial cell lines before conducting inflammasome experiments and the need to work in mouse and human primary cells.…”
Section: The Inflammasome: a Well‐regulated Immune Platform Also Presmentioning
confidence: 99%
“…These findings suggest that B. thailandensis is generally well controlled by cell-autonomous immunity in mammals. While GBPs appear to play a minor role in direct promotion of inflammasome activation, previous studies have established an important role for many inflammasome signaling components and the downstream inflammatory cytokines in both protection and immunopathology during B. thailandensis and B. pseudomallei infections [8][9][10]31,42]. Many pathogens encode bacterial factors that nucleate actin polymerization that is dependent upon the Arp2/3 complex [43].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Burkholderia thailandensis is an opportunistic intracellular pathogen that induces multinucleated giant cell (MNGC) formation in macrophage cell lines and is utilized as a model organism for the related and highly virulent B. pseudomallei and B. mallei, which are considered potential bioweapons [5][6][7]. Previous studies have also shown that Burkholderia infections are critically controlled by multiple inflammasomes, pyroptotic cell death, and the pyroptosisregulated inflammatory cytokine IL-18 [8][9][10]. Burkholderia infection-induced pathology is also mediated by excessive release of pyroptosis-regulated IL-1β.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages play various roles in different stages of diseases due to their heterogeneity 6 . At the early stage of pathogens, activated macrophages release a lot of pro‐inflammatory cytokines, including interleukin (IL)‐1β and IL‐18 7,8 . Macrophages undergo inflammatory programmed cell death, called pyroptosis, at the late stage of inflammatory response under certain pathological stimulations 9‐11 .…”
Section: Introductionmentioning
confidence: 99%